2022
DOI: 10.3389/fmed.2022.751617
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pulmonary Aspergillosis Diagnosis via Peripheral Blood Metagenomic Next-Generation Sequencing

Abstract: Invasive pulmonary aspergillosis (IPA) is one of the major causes of morbidity and mortality in immunocompromised patients such as hematological malignancies, hematopoietic stem cell transplantation, and solid organ transplantation. The diagnosis of IPA in these patients is still difficult because it has no obvious specificity in clinical symptoms, signs and imaging, and test sensitivity of blood 1,3-β-d-glucan test, galactomannan are low. Therefore, we still need to explore more diagnostic methods. In our stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
6
1
Order By: Relevance
“…Mixed infections and co-pathogens in 13 non-neutropenic pulmonary aspergillosis cases identified using mNGS. and the diagnosis of pulmonary aspergillosis (He et al, 2019;Zhang et al, 2020;Chen et al, 2021;Ma et al, 2022). In these studies, Chen et al (Chen et al, 2021) and Zhang et al (Zhang et al, 2020) reported the application of NGS in diagnosing coinfection of Aspergillus and P. jirovecii, which supports the results of this study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Mixed infections and co-pathogens in 13 non-neutropenic pulmonary aspergillosis cases identified using mNGS. and the diagnosis of pulmonary aspergillosis (He et al, 2019;Zhang et al, 2020;Chen et al, 2021;Ma et al, 2022). In these studies, Chen et al (Chen et al, 2021) and Zhang et al (Zhang et al, 2020) reported the application of NGS in diagnosing coinfection of Aspergillus and P. jirovecii, which supports the results of this study.…”
Section: Discussionsupporting
confidence: 82%
“…To date, mNGS has been clinically used. There are only few studies that have investigated the association between mNGS and the diagnosis of pulmonary aspergillosis ( He et al., 2019 ; Zhang et al., 2020 ; Chen et al., 2021 ; Ma et al., 2022 ). In these studies, Chen et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the early diagnosis of pulmonary trichomycosis lacks speci city and relies mainly on histopathology and fungal culture, with long lead times and low positive rates [7]. In recent years, with the advent of mNGS assays, the detection rate of pathogenic organisms in children with postchemotherapy coinfection in leukemia has improved [8]. In this study, we retrospectively analyzed seven children with acute leukemia who had early infection detected by the mNGS method after chemotherapy for leukemia from January 2020 to December 2021, and analyzed the clinical characteristics, treatment, and outcome of these children [9].…”
Section: Introductionmentioning
confidence: 99%
“…The most severe form of Aspergillus infection is invasive aspergillosis (IA), which affects more than 300,000 people worldwide every year [ 10 ]. IPA accounts for more than 90% of cases of IA, and viral infections such as infections with SARS-CoV-2 and influenza viruses have recently been reported to be risks for IPA [ 7 , 11 ]. Influenza virus infection is known to induce 'influenza-associated pulmonary aspergillosis (IAPA)', which can progress to IPA, and the incidence of IAPA has been increasing [ 5 , 6 ].…”
Section: Discussionmentioning
confidence: 99%